Combined mutation differential evolution to solve systems of nonlinear equations - Ramadas, Gisela C. V. (2013)
This paper presents a differential evolution heuristic to compute a solution of a system of nonlinear equations through the global optimization of an appropriate merit function. Three different mutation strategies are combined to generate mutant points. Preliminary numerical results show the effectiveness of the presented heuristic.